STUDI KOMPARATIF RUKUN DAN SYARAT PERKAWINAN DALAM PERSPEKTIF FIQH KLASIK DAN NEGARA MESIR - Alfi Karomah; Muhammad Abror Suriyanto; Ahmad Izzuddin (Makkah: Journal Of Islamic Studies, 2025)
This study aims to analyze the pillars and conditions of marriage from the perspectives of Islamic jurisprudence (fiqh) and Egyptian positive law, and to compare them within the framework of contemporary Islamic family law. The focus of the analysis is directed at identifying both the differences and similarities in the views of Islamic legal schoolsparticularly the Hanafi schooland the regulation of marriage law in Egypt, which has undergone processes of codification and modernization. This research employs a normative legal research method with a comparative approach, drawing upon classical fiqh literature, Egyptian statutory regulations, and relevant contemporary scholarly works. The findings indicate that Egyptian marriage law substantively adopts the principles of Hanafi fiqh, while simultaneously introducing adjustments through the establishment of a minimum age for marriage, the mandatory registration of marriage, and the strengthening of legal protection for women and children. From a comparative perspective, it can be concluded that Egyptian marriage law represents a model of integration between Islamic legal norms and modern state law. Therefore, an integrative approach that combines madhhab-based fiqh, maqāṣid al-sharī‘ah, and the demands of positive law is essential to maintain the relevance and legitimacy of Islamic family law in addressing contemporary social challenges.